Vitamin C in fleshy fruits: biosynthesis, recycling, genes, and enzymes - D. Y. Tyapkina; E. Z. Kochieva; M. A. Slugina (Вавиловский журнал генетики и селекции)
L-ascorbic acid (vitamin C) is a plant secondary metabolite that has a variety of functions both in plant tissues and in the human body. Plants are the main source of vitamin C in human nutrition, especially citrus, rose hip, tomato, strawberry, pepper, papaya, kiwi, and currant fruits. However, in spite of the biological significance of L-ascorbic acid, the pathways of its biosynthesis in plants were fully understood only in 2007 by the example of a model plant Arabidopsis thaliana. In the present review, the main biosynthetic pathways of vitamin C are described: the L-galactose pathway, L-gulose pathway, galacturonic and myo-inositol pathway. To date, the best studied is the L-galactose pathway (Smyrnoff–Wheeler pathway). Only for this pathway all the enzymes and the entire cascade of reactions have been described. For other pathways, only hypothetical metabolites are proposed and not all the catalyzing enzymes have been identified. The key genes participating in ascorbic acid biosynthesis and accumulation in fleshy fruits are highlighted. Among them are L-galactose pathway proteins (GDP-mannose phosphorylase (GMP, VTC1), GDP-D-mannose epimerase (GME), GDP-L-galactose phosphorylase (GGP, VTC2/VTC5), L-galactose-1-phosphate phosphatase (GPP/VTC4), L-galactose-1-dehydrogenase (GalDH), and L-galactono1,4-lactone dehydrogenase (GalLDH)); D-galacturonic pathway enzymes (NADPH-dependent D-galacturonate reductase (GalUR)); and proteins, controlling the recycling of ascorbic acid (dehydroascorbate reductase (DHAR1) and monodehydroascorbate reductase (MDHAR)). Until now, there is no clear and unequivocal evidence for the existence of one predominant pathway of vitamin C biosynthesis in fleshy fruits. For example, the L-galactose pathway is predominant in peach and kiwi fruits, whereas the D-galacturonic pathway seems to be the most essential in grape and strawberry fruits. However, in some plants, such as citrus and tomato fruits, there is a switch between different pathways during ripening. It is noted that the final ascorbic acid content in fruits depends not only on biosynthesis but also on the rate of its oxidation and recirculation.